Pallid Disc Oedema in a Young Patient: Clinical and Diagnostic Challenge. (4th March 2022) - Dedina, Liana; Hassall, Mark M.; Jesudason, Shilpanjali; Simon, Sumu
ABSTRACT: A mid-thirties male with end-stage renal failure receiving haemodialysis on a background of four failed renal transplants, post-transplant lymphoproliferative disorder, and autonomic dysfunction presented with acute vision change in his left eye. Over days his vision in that eye deteriorated from 20/25 to no light perception. Given his complex medical background he was extensively investigated for infective, inflammatory, infiltrative and vasculitic aetiologies to explain acute vision loss with pallid disc swelling. A final diagnosis of non-arteritic anterior ischaemic optic neuropathy secondary to refractive hypotension and haemodialysis was reached.